Iron Metabolism in Young Female Rats With Low Bone Mineral Density Induced by Food Restriction and Running Exercise. (14th June 2022) - Kioka, Kazuki; Aikawa, Yuki; Yamamoto, Hayata; Sugiyama, Kaya; Noboritate, Kota; Shingu, Hana; Suzuki, Hirotaka; Omi, Naomi
Abstract: Objectives: It has been reported that more than 30% of female endurance athletes suffer from sports disorders such as fatigue fractures and anemia. This is due to excessive physical activity and extreme dietary restrictions to improve athletic performance. Deficiency of energy and nutrients leads to low energy availability, which causes various health problems. In recent years, it has been reported that bone health and iron deficiency interact via the endocrine system, suggesting that fatigue fractures and anemia may develop in association with each other. The purpose of this study was to determine iron metabolism in young female rats with low bone mineral density (BMD) induced by a combination food restriction under running exercise. Methods: Five-week-old Sprague-Dawley female rats were acclimatization period for 1 week and acclimated to treadmill running for 10 days. After that, the animals were divided into seven groups: the sedentary and ad libitum feeding (group F) and fed 90%, 70%, and 50% of the 3-day average of group F food intake in the sedentary (SED) or running exercise (EX) condition. Treadmill running exercise was performed at 25 m/min for 30 minutes. Fifteen days after the start of food restriction, blood and tibia were collected. The tibia was measured for BMD using the dual-energy x-ray absorptiometry method. The blood was measured for blood cell composition, serum iron, and ferritin. A two-way analysis of variance was used to examine the main effects and interactions of exercise and food restriction in six groups, excluding group F. We also evaluated the relationship between BMD of tibia and serum iron using Pearson's product fraction correlation coefficient. Results: Food restriction had significant main effects on causing lower body weight, BMD of tibia, and ferritin. Moreover, food restriction had significant main effects on causing higher serum iron. On the other hands, there were no significant main effects of food restriction on red blood cell corrected for hematocrit. There was a significant negative correlation between BMD of tibia and serum iron. Conclusions: Our study suggests that a food restriction increases serum iron in young female rats under running exercise condition and there is a correlation between low BMD and high serum iron. Funding Sources: Funding from the scientific research of University of Tsukuba.